Pelatihan Bahasa Inggris menggunakan E-learning bagi Anak Pekerja Pabrik Batu-Bata di Gampong Kajhu - Maulana, Riyan; Ahmad, Adi; Mujiburrahman; Akbar, Rizaldi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
This service involves village community leaders and village communities including children, youth, and community leaders. This method is carried out to understand the Kajhu community about: a) the weaknesses they experience and have, b) the community's desire to overcome their shortcomings, c) develop strategies and methods to solve problems, and d) help the community overcome, solve, and think critically to get a solution to the problem when learning English. Based on the implementation of KKN, it is known that 1) the people of Kajhu Village provide maximum support through enthusiastic participation and facilitation of community service activities, 2) community service training materials that are in accordance with community needs encourage enthusiasm for English language training, and 3) optimism for the realization of an English Club. in Kajhu Village is very high, which is shown by the seriousness of each party in participating in the process of activities carried out.